Capital Structure Determinants in German SMEs: Panel Analysis and Policy Recommendations - Teona Shugliashvili; Erekle Pirveli; Tea Munjishvili; Fitim Deari (Credit and Capital Markets – Kredit und Kapital, 2023)
This study investigates the financing decisions within German SMEs, examining firm-specific, macroeconomic, and news-related determinants. Utilizing a 10-year dataset encompassing 13,051 SMEs, we employ a dynamic panel data model with an unbiased Dynamic Panel Fractional (DPF) estimator to identify the key variables influencing the debt-to-equity ratio. The findings underscore the importance of factors such as the non-debt tax shield, firm size, interest rate spread, and the economic policy uncertainty index. The study's findings propose the following policy implications: 1) Policy initiatives targeting firm size and non-debt tax shields affect SME leverage; 2) Policies addressing the term spread and economic uncertainty influence debt levels across various German industries; 3) Industry-specific SME policies are advisable, due to the significant industry effects on German SME leverage; 4) SME policy incentives yield short-term effects on capital structures, as SMEs adjust leverage within 8 months.
Keywords: G32; G38; L25; L26; M13; C23; 330; SME policy; capital structure; SMEs; financing decisions; leverage; panel data